The Youth Language as Witness of Changes in Albania after ‘90s (European Journal of Language and Literature, 2015)
Language is a communication and expression tool which at any time and in any society is presented in different versions in dependence of many factors. In sociolinguistic viewpoint when we investigate the links between language and social context, is noted that the language is very diverse, changes in time, in space, in different classes or social strata and in concrete situations. This paper aims to present a comparative view between youth slang, namely the vocabulary used by them in Albania before the 90s with the one after '90s. We tried to argue that the language is made in certain circumstances, especially under the pressure of factors out-linguistic, witness or mirror of the social mentalities. However, this is a superficial treatment, which will be the subject of a more detailed research in the future.